Optimization of Spirulina platensis Culture Media as an Effort for Utilization of Pangasius Farming Waste Water - Marini Wijayanti; Dade Jubaedah; Nuni Gofar; Devi Anjastari (Sriwijaya Journal of Environment, 2019)
Pangasius is a fast-growing fish species that has great potential for production and export growth in Indonesia. Their farming produces a lot of organic material and ammonia which potentially make polution in freshwater body. The wastewater can be used for high value microalgal cultivation media.  The microalgae are used in various fields, one of those is Spirulina platensis, a spiral blue green algae.  This aims of this study was to determine the best composition of the technical fertilizer in the pond waste of Pangasius farming pond to obtain maximum density and know the spesific growth rate of Spirulina platensis. The research method used Completely Randomized Design (CRD) with 6 treatments (3 replication), P0 using 100% technical fertilizer without using Pangasius waste water while P1-P5 use 0% (P1), 25% (P2), 50% (P3), 75% (P4) and 100% (P5) technical fertilizer using Pangasius farming waste water. The most efficient treatment obtained 23.90 gL-1 maximum density, 6.22%.d-1 specific growth rate and 87.77% ammonia removal.